Association between periodontal disease and preterm prelabour rupture of membranes. (3rd February 2019) - Radochova, Vladimira; Stepan, Martin; Kacerovska Musilova, Ivana; Slezak, Radovan; Vescicik, Peter; Menon, Ramkumar; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective: Periodontal disease is a possible contributing factor to preterm delivery. The aim of this study was to compare the periodontal status of women with preterm prelabour rupture of membranes (PPROM) and women with uncomplicated singleton pregnancies. Patients and Methods: Seventy‐eight women with PPROM at gestational ages between 24 + 0 and 36 + 6 weeks and 77 healthy women with uncomplicated pregnancies, matched for gestational age at sampling without preterm birth, were included in this study. All women underwent evaluation of periodontal and oral hygiene status. Results: Women with PPROM had higher gingival and plaque indexes in crude analysis (gingival index: median 0.80 versus 0.20; p < 0.0001; plaque index: median 0.80 versus 0.10; p < 0.0001), even after adjustment for smoking status ( p < 0.0001 and p < 0.0001). Mean clinical attachment loss (CAL) and probing pocket depth (PPD) values were higher in women with PPROM in the crude analysis (CAL: median 2.3 mm versus 1.8 mm; p < 0.0001; PPD: median 2.3 mm versus 1.8; p < 0.0001), as well as after adjustment for smoking status ( p < 0.0001 and p < 0.0001). Conclusions: Pregnant women with PPROM residing in central Europe had worse periodontal status than women with uncomplicated pregnancies.